2018
DOI: 10.1016/j.jpowsour.2018.06.097
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nickel agglomeration on Solid Oxide Cell operated in fuel cell and electrolysis modes

Abstract: Long-term experiments have been carried out to investigate the impact of Nickel (Ni) coarsening on the performance of Solid Oxide Cell. Durability tests have been performed with H2 electrode supported cells at 850 °C and 750 °C in fuel cell and electrolysis modes. Microstructural changes in the composite electrode of Nickel and Yttria Stabilized Zirconia (YSZ) have been characterized by synchrotron X-ray nanotomography. Analysis of the reconstructions have revealed that Ni coarsening induces a significant decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
113
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 72 publications
11
113
0
Order By: Relevance
“…This results in the smaller decrease of YSZ/Ni interface area when compared to the decrease of Pore/Ni interface area ( Table 2). The Ni rearrangements observed in the cell investigated in this work are well in line with the observations of Hubert et al [42] where the inhibiting effect of the YSZ skeleton on Ni coarsening at typical SOC operating temperature was pointed out. The homogenization of microstructural parameters as observed here after one year of electrolysis operation leads to the tentative conclusion that the different conditions experienced by the cell at the two extremities are more important in the first hundreds of hours of cell life.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This results in the smaller decrease of YSZ/Ni interface area when compared to the decrease of Pore/Ni interface area ( Table 2). The Ni rearrangements observed in the cell investigated in this work are well in line with the observations of Hubert et al [42] where the inhibiting effect of the YSZ skeleton on Ni coarsening at typical SOC operating temperature was pointed out. The homogenization of microstructural parameters as observed here after one year of electrolysis operation leads to the tentative conclusion that the different conditions experienced by the cell at the two extremities are more important in the first hundreds of hours of cell life.…”
Section: Discussionsupporting
confidence: 92%
“…The results for Pore/Ni and YSZ/Ni interface area summarized in Table 2 show a decrease of approximately 69 % and 29 %, respectively, when comparing the inlet side of the tested cell with the reference cell. The difference in the extend of the decrease can be related to the inhibiting effect of YSZ on Ni coarsening as discussed in [40,42]. Huber et al [42] observed that the morphological variation of nickel during the coarsening process is more pronounced on the Ni surface in contact with the gas phase than at the YSZ/Ni interface.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that kinetics for H 2 or CO oxidization are slightly faster than for H 2 O or CO 2 reduction [13,14]. At the Ni-YSZ electrode, beside loss of contact between Ni and Ni grain due to Ni agglomeration or Ni migration [19,20,28], nano ZrO 2 precipitation from Zr dissolved in the Ni bulk was observed [29,30]. In SOFC mode the process is highly exothermic, while in SOEC mode it is dependent on the operation voltage whether heat is produced or consumed in the electrolysis overall process (considering both reaction entropy changes and joule heat).…”
Section: Introductionmentioning
confidence: 99%
“…However, when operating the SOEC at high electrolysis current density (above 1 A cm -2 ) or correspondingly high over-potential, severe degradation has been widely reported [17][18][19][20][21][22][23][24][25][26][27]. At the Ni-YSZ electrode, beside loss of contact between Ni and Ni grain due to Ni agglomeration or Ni migration [19,20,28], nano ZrO 2 precipitation from Zr dissolved in the Ni bulk was observed [29,30]. The formation of small cavities inside YSZ grains and -[ * ] Corresponding authors, xisu@dtu.dk (X.…”
Section: Introductionmentioning
confidence: 99%
“…Ni agglomeration is inevitable for Ni–YSZ cathode during long‐term stability test because the growth of Ni particles is thermally induced at high temperatures and independent of the applied voltage or gas composition . After 2000 h of SOEC operation at 850 °C, the mean diameter of Ni particles increases from 0.96 to 1.16 µm, with the tortuosity factor changing from 7.45 to 8.27 ( Figure A) . Ni agglomeration significantly decreases the length of TPBs and the specific surface areas of Ni/gas, and finally contributes to about 20–25% of the total degradation in SOEC at 850 °C after 1000–2000 h of operation.…”
Section: Degradationmentioning
confidence: 99%